2007
DOI: 10.1111/j.1567-1364.2007.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

ReprogrammingHansenula polymorphafor penicillin production: expression of thePenicillium chrysogenum pclgene

Abstract: We aim to introduce the penicillin biosynthetic pathway into the methylotrophic yeast Hansenula polymorpha. To allow simultaneous expression of the multiple genes of the penicillin biosynthetic pathway, additional markers were required. To this end, we constructed a novel host-vector system based on methionine auxotrophy and the H. polymorpha MET6 gene, which encodes a putative cystathionine beta-lyase. With this new host-vector system, the Penicillium chrysogenum pcl gene, encoding peroxisomal phenylacetyl-Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
(41 reference statements)
0
17
0
Order By: Relevance
“…3). We previously showed that both heterologous proteins are properly synthesized and sorted in H. polymorpha [8], [9]. To test whether HpPen4 cells produced and secreted the β-lactam antibiotic penicillin G (PenG), cells were grown in media supplemented with AAA and phenylacetic acid (PAA), the PenG side chain precursor.…”
Section: Resultsmentioning
confidence: 99%
“…3). We previously showed that both heterologous proteins are properly synthesized and sorted in H. polymorpha [8], [9]. To test whether HpPen4 cells produced and secreted the β-lactam antibiotic penicillin G (PenG), cells were grown in media supplemented with AAA and phenylacetic acid (PAA), the PenG side chain precursor.…”
Section: Resultsmentioning
confidence: 99%
“…In P. chrysogenum, microbodies (peroxisomes) are essential for penicillin biosynthesis because the two final enzymatic steps catalyzed by acyl-CoA:isopenicillinN acyltransferase 28 and phenylacetyl-CoA ligase 29 are located in these organelles. Moreover, high-producing strains have enhanced microbody volume fractions (Fig.…”
Section: Microbodiesmentioning
confidence: 99%
“…Microbodies are organelles involved in the final steps of the penicillin pathway, which are catalyzed by the acyl-coenzyme A: isopenicillin N acyltransferase (IAT) and phenylacetyl-CoA ligase [18, 55, 56]. In fact, it has been reported that microbody volume fractions are enhanced in high-producing strains [57].…”
Section: Classical Strain Improvement and Molecular Genomic-transcmentioning
confidence: 99%